Comprehensive basic education: a means for enhancing disadvantaged children access to education and sustainable development in Nigeria (2010)
Education is a right for all, especially for children because through education, children acquire relevant knowledge, skills and increased capacity for work which are required for national development. It is the key with which the door of literacy is opened while simultaneously closing the gate of ignorance, poverty and diseases that could plaque a nation. It will be disadvantageous therefore, if a category of children called disadvantaged children are deprived of their right to education which is capable to make them live happily among others in the society, earn their livelihood and contribute significantly to national advancement. This paper, therefore, looks at disadvantaged children, their right to basic education, the gains that could be derived in educating them as well as steps to enhancing their access to education.